(untitled) (Texas Journal of Engineering and Technology, 2022)
At a time when food security is on the rise in the world, it is important to study the demand for bread and bakery products in Uzbekistan, to identify factors affecting the demand for bread and bakery products. Based on this, marketing research was conducted to study the demand of the population for bread and bakery products. Some results of it are given in this article.